Ferroptosis in lymphoma: Emerging mechanisms and a novel therapeutic approach - Zhou, Qiao; Li, Ting; Qin, Qin; Huang, Xiaobo; Wang, Yi (Frontiers in Genetics, 2022)
Ferroptosis represents a new type of cell death that is different from other cell death, such as apoptosis, necroptosis, autophagy, and pyroptosis. It is accompanied by a large amount of iron accumulation and lipid peroxidation during the cell death process and preserves its distinguishable morphological, biological, and genetic features. There are many factors that can directly or indirectly affect iron metabolism, lipid metabolism and accumulation of lipid reactive oxygen species (ROS) through different pathways. Recent studies show that ferroptosis plays a crucial role in the occurrence, development, and treatment of hematological malignancies, such lymphoma. Despite the emergence of new targeted agents, the molecular heterogeneity of lymphoma remains to be a major therapeutic challenge currently. Since lymphoma is associated with ferroptosis and sensitive to ferroptosis, targeting potential regulatory factors in the ferroptosis pathway may promote or inhibit the disease progression of lymphoma and has become an active and challenging topic of research. This review will summarize the key molecular mechanisms of ferroptosis and the current potential relationships between ferroptosis with lymphoma. It is expected to provide novel therapeutic potential of ferroptosis as the target for lymphoma.